Early Outcome of Off-Pump Versus Conventional Coronary Artery Bypass Grafting Surgery in Patients with Multivessel Coronary Artery Disease in a Specialized center in Bangladesh - Reza, Amina; Alam, AKM Manzurul; Islam, Md Shafiqul; Hossain, Abdullah Al Mamun; Rahman, Md Mizanur; Islam, Md Amirul; Siddiqi, Nurul Alam; Shimul, Md Shahriar Kabir; Nur, M Asmaul Alam; Ahmed, Masud; et al. (Cardiovascular Journal, 2023)
Background: Both off-pump (OPCAB) and on pump arrest heart coronary artery bypass surgery (CABG) are frequently performed in department of cardiac surgery, NICVD, Dhaka, Bangladesh. Both types of procedures have advantages and disadvantages. This study was conducted to analyze early post-operative outcome following both types of CABG on patients with multivessel coronary artery disease. Methods: Between 1st September 2019 to 28th February 2021, a cross-sectional study was performed with total 60 patients. 30 patients underwent Off Pump coronary artery bypass grafting (OPCAB)(Group A) and 30 patients underwent Conventional Coronary Artery Bypass (CCAB) (Group B) surgery. Preoperative, peroperative and post-operative variables were recorded and analyzed with appropriate statistical tools and p ≤ 0.05 considered statistically significant. Results: Fifty-five male i.e., 91.67% and five female i.e., 8.33% of total patients were participated in this study. Mostly were within forty-five to sixty-four years age group. Preoperative risk factors, family history and drug history had no significant difference (p>0.05). Mean ± SD number of bypass conduits given in each group almost similar and no statistically significant arrhythmia in terms of atrial fibrillation (AF), ventricular tachycardia (VT) and premature ventricular contraction (PVC) were found preoperatively (p>0.05). New onset of early post-operative ECG changes was found in 3 patients of group A and 9 in group B (10 % vs 30%). AF and PVC found in group B significantly (p<0.05) higher than group A. Immediate post-operative troponin I was higher in group B (p = 0.001). Mean ± SD duration of mechanical ventilation, inotropic supports, ICU stay, bleeding and blood transfusion and serum creatinine were significantly higher in group B (p <0.05). Overall immediate and follow up post-operative morbidities were higher in group B than A (p<0.05). Conclusion: Although on pump arrest heart CABG still stands gold standard, in our study we found OPCAB is better than conventional method. Cardiovasc j 2023; 16(1): 1-8